2003
DOI: 10.1016/s0928-8244(03)00126-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of matrix metalloproteinases 1 and 3 by smooth muscle cells upon infection withChlamydia pneumoniae

Abstract: Atherosclerosis has been linked to Chlamydia pneumoniae infection. In atherosclerotic arteries chlamydiae infect macrophages, endothelial cells, and smooth muscle cells (SMC). It has been suggested that the proteolysis of the extracellular matrix by matrix metalloproteinases (MMPs) is involved in the destabilisation and rupture of atherosclerotic plaques. In this study we investigated the expression of several MMPs and tissue inhibitors of MMP (TIMPs) in C. pneumoniae-infected SMC using reverse transcription-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
2
28
0
1
Order By: Relevance
“…In addition to their commonly known natural target cells such as epithelial/fibroblast cells and macrophages, chlamydiae can also infect other organ-specific cells, including astrocytes (Dreses-Werringloer et al, 2006;Levitt et al, 1986) and muscle cells (Dumrese et al, 2005;Rodel et al, 2003;Yang et al, 2005). We have recently shown that both C. trachomatis and C. pneumoniae can replicate in neonate heart muscle cells (Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to their commonly known natural target cells such as epithelial/fibroblast cells and macrophages, chlamydiae can also infect other organ-specific cells, including astrocytes (Dreses-Werringloer et al, 2006;Levitt et al, 1986) and muscle cells (Dumrese et al, 2005;Rodel et al, 2003;Yang et al, 2005). We have recently shown that both C. trachomatis and C. pneumoniae can replicate in neonate heart muscle cells (Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Total RNA was prepared using an RNeasy Mini Kit (Qiagen, Hilden, Germany). Reverse transcriptase PCR (RT-PCR) was carried out as described previously (35). The sequences of specific primers used in this work are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Because C. pneumoniae infection stimulates the production of matrix metalloproteinases (MMPs) the pathogen may promote increased matrix protein turnover in the airways during respiratory infection (35,40). It can also be hypothesized that C. pneumoniae may contribute to airway remodeling in COPD and asthma by modulating the synthesis of interstitial collagens and fibronectin.…”
mentioning
confidence: 99%
“…Human vascular SMC (C-12511; PromoCell, Heidelberg, Germany) were infected with C. pneumoniae TW-183 (obtained from the Institute of Ophthalmology, London, United Kingdom) at a multiplicity of infection (MOI) of 5 as previously described (17). For heat inactivation, chlamydial suspensions were held at 75°C for 10 min prior to inoculation onto cell monolayers.…”
mentioning
confidence: 99%
“…In some experiments, mock-infected and infected SMC were treated with NS-398 {N-[2-(cyclohexyloxy)-4-nitrophenyl]-methanesulfonamide; Qbiogene-Alexis, Grünberg, Germany}. Chlamydial inclusions in infected cultures were visualized by immunofluorescence staining as previously described (17). Conditioned media from infected and mock-infected cultures were collected at 2, 24, 48, and 72 h after infection and clarified by centrifugation at 20,000 ϫ g for 30 min before inoculation onto uninfected SMC.…”
mentioning
confidence: 99%